2015
DOI: 10.1021/acscatal.5b00996
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activity of Immobilized or Chemically Modified Enzymes

Abstract: Re-engineering enzymes with high activities in the given environments different from the physiological one has been constantly pursued for application of enzymatic catalysis in industrial biocatalytic processes, pharmaceutical industry, biosensing, etc. Re-engineering enzyme catalysts by chemical approaches, including immobilization and chemical modification, represents a simple but effective route. The unusual phenomenon that immobilized or chemically modified enzymes display higher activities than native enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
264
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(268 citation statements)
references
References 144 publications
(151 reference statements)
2
264
0
2
Order By: Relevance
“…Recent developments have showed that enzymes have not been immobilized only on micro sized materials but also immobilized on various types and shapes of nano sized materials, such as nano spheres, fibers, tubes and pores. The support materials used in immobilization should have functional groups, insolubility in water, biocompatibility and a large surface area [2,8]. Although immobilizations make enzymes highly stable against environmental changes, reusable and economical, most of enzymes inevitably lose their catalytic activities after immobilization due to mass transfer limitations between the enzyme and substrate and unfavorable conformation [14,15].…”
Section: Immobilization Of Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments have showed that enzymes have not been immobilized only on micro sized materials but also immobilized on various types and shapes of nano sized materials, such as nano spheres, fibers, tubes and pores. The support materials used in immobilization should have functional groups, insolubility in water, biocompatibility and a large surface area [2,8]. Although immobilizations make enzymes highly stable against environmental changes, reusable and economical, most of enzymes inevitably lose their catalytic activities after immobilization due to mass transfer limitations between the enzyme and substrate and unfavorable conformation [14,15].…”
Section: Immobilization Of Enzymesmentioning
confidence: 99%
“…The substrate specificity, low toxicity and the absence of production of undesirable products make enzymes have advantages over chemical catalysts in industrial applications [4]. Despite of these unique propeties of free enzymes, but easy degradation on their molecular structure at high temperatures, at acidic or 4 basic pHs and in the presence of organic solvents strictly limite their use [6,8]. They can not also be seperated and gained from the reaction medium to be re-used.…”
Section: Introductionmentioning
confidence: 99%
“…High enzyme stability is important for applications. 3 Deactivation of enzymes by high temperature and extreme pH are the major reasons for enzyme deactivation. The stability of the GOx&HRP@Zn/AMP nanofibers was examined in at different pH (from 7.4 to 10, Figure 5a) and temperature (from 25 to 90 C, Figure 5b) and compared to that of the free GOx and HRP in solution.…”
mentioning
confidence: 99%
“…The water solubility and/or insolubility, biocompatibility, surface functionality and size and morphology are ciritcal features to choose the supports for immobilization. Using various external supports generally enabled us to arrange amount of immobilized enzymes and to reuse them [2,17]. Despite all these developments, most of immobilized enzymes have showed great stabilities towards environmental conditions (temprature, pH values etc.…”
Section: Conventional Immobilization Techniquesmentioning
confidence: 99%
“…While enzymes may react with one or a few substrates due to their substrate specificity, they may catalyze whole substrate or their certain parts [1][2][3]. However despite these advantages, short live time in aqueous and organic medium, quick loss of activity (at high temperatures, at acidic or basic pHs and high salt concentration), and lack of separation from reaction medium and reusability are potential disadvantages of free enzymes and which make them quite expensive and highly suppress their use in diverse range of applications [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%